I miss you when I blink : Dispatches from a relatively ordinary life - Philpott, Mary Laura (Murdoch Books, 2019)
"Mary Laura Philpott thought she'd cracked the code: Always be right, and you'll always be happy. But once she'd completed her life's to-do list (job, spouse, house, babies--check!), she found that instead of feeling content and successful, she felt anxious. Lost. Stuck in a daily grind of overflowing calendars, grueling small talk, and sprawling traffic. She'd done everything "right," but she felt all wrong. What's the worse failure, she wondered: smiling and staying the course, or blowing it all up and running away? And are those the only options? In this memoir-in-essays full of spot-on observations about home, work, and creative life, Philpott takes on the conflicting pressures of modern adulthood with wit and heart. She offers up her own stories to show that identity crises don't happen just once or only at midlife; reassures us that small, recurring personal re-inventions are both normal and necessary; and advises that if you're going to faint, you should get low to the ground first. Most of all, Philpott shows that when you stop feeling satisfied with your life, you don't have to burn it all down and set off on a transcontinental hike (unless you want to, of course). You can call upon your many selves to figure out who you are, who you're not, and where you belong. Who among us isn't trying to do that? Like a pep talk from a sister, I Miss You When I Blink is the funny, poignant, and deeply affecting book you'll want to share with all your friends, as you learn what Philpott has figured out along the way: that multiple things can be true of us at once--and that sometimes doing things wrong is the way to do life right"--